A study on the effect of macroeconomic variables toward the performance of Kuala Lumpur Composite Index (KLCI) / Abdul Fatah Ahmad - Ahmad, Abdul Fatah (2007)
The study was conducted to find out the significant relationship between macroeconomic variables with Kuala Lumpur Composite Index. The variables selected are economic growth, inflation, interest rate and exchange rate. For the interest rate, Base Lending Rate has been used as the indicator. Meanwhile, the exchange rate used is the Japanese currency (YEN). The method used for this study is the regression analysis. The result then has been interpret base on the correlation, coefficient correlation, Durbin-Watson, F-statistic and T-statistic. The data used for the study are collected for the period of fifteen year and using the monthly data from 1991 to 2005. Base on the result, it was conclude that the economic growth and exchange rate are not significant to the KLCI. However, there are significant relationship between inflation and interest rate to the KLCI. Inflation rate has a positive relationship, meanwhile interest rate has a negative relationship with KLCI.